The power of woman-to-woman mentorship in creating long-term changes in biodiversity conservation in Southeast Asia - Sheherazade,; Tsang, Susan M.; Lanusi, Asnim Alyoihana (Frontiers in Conservation Science, 2022)
Growing evidence indicates that women’s involvement and leadership are important to creating inclusive conservation programs, increasing likelihood of success, and achieving sustainability. Effective future women leaders can be created by providing them with dedicated mentorship, as in long-term support and dynamic learning that encompass the entirety of a person, not only their technical training. Mentorship by women is key to ensuring more women are empowered, can advance their careers, and become independent leaders in their domains. The ways mentorship contribute to a woman’s career have been frequently studied in medicine, sports, and education, yet rarely in conservation. Providing real examples of long-term mentorships centered on the perspective of a mentee from the Global South will demonstrate an applicable roadmap towards recruiting and retaining women in conservation. We recount two sets of ten-year long mentor-mentee relationships—one with a foreign mentor and the other domestic—based on our personal experiences in Indonesia. We examined issues raised by Indonesian women in conservation and provided targeted solutions that may be applicable to a broader audience. The resulting group of empowered, capable women can rely on one another for technical and moral support, along with work together to shift social norms towards becoming more inclusive of women in more varied roles and at multiple career levels in conservation. In highlighting real examples, mentees can understand what they should seek out and expect from mentorship, and how women from the Global North and Global South can provide true mentorship to more women without access to the same opportunities. We hope to inspire more women from the Global South to continue their careers and be leaders in conservation.